Upaya Promotif Dan Preventif Stunting Kepada Pengunjung Posyandu RW 3 Kelurahan Mojosongo, Kecamatan Jebres, Kota Surakarta - Rhama Syuhada Sujak; Agus Widodo; Anis Dwi Charisa (Universitas 45 Surabaya, 2024)
Introduction: According to WHO (2015), stunting is a disruption in the growth and development of children due to chronic malnutrition and recurrent infections, which are characterized by body length or height below standard. Furthermore, according to WHO (2020) stunting is short based on length/height according to age which is less than -2 standard deviation (SD) on the WHO child growth curve which occurs due to irreversible conditions due to inadequate nutritional intake and/or recurrent infections/chronic disease that occurs within 1000 first-time days of life. Mojosongo is one of the Villages in Jebres District, Surakarta City. Based on the jateng.prov.go report in 2022, in Mojosongo there are 137 stunting cases that will be handled. Wrong parenting patterns, inappropriate feeding, high cases of young marriages, and lack of knowledge cause the risk of stunting in children. Reflecting on these conditions, this area was chosen to be the target of promotive and preventive efforts in carrying out willing to make the pulic of Indonesia healthier Objective: This activity aims to increase general public understanding about stunting in children. Method: Activities with lecture speaking and give education through leaflet media. Evaluation using a questionnaire both before counseling and after presenting the material.